GERAKAN AYO SEKOLAH DI KABUPATEN BOJONEGORO: PENINGKATAN SUMBER DAYA MANUSIA MELALUI PENDIDIKAN UNTUK MENYONGSONG BONUS DEMOGRAFI - Sonyaruri Satiti (Jurnal Kependudukan Indonesia, 2019)
Improving the quality of human resources through education is one of the ways to benefit from the window of opportunity. The Government of Indonesia and many local governments have been conducting programs to provide easier access to education to prevent dropouts. The Local Government of Bojonegoro has been implementing a program called "Ayo Sekolah" to curb dropouts. This paper aims to describe the conditions of education in Bojonegoro District and the implementation of the â€œAyo Sekolahâ€ Program in Bojonegoro District. The analysis is based onÂ  the result of research on the program. The research used a quantitative and qualitative approach. Qualitative data is collected through in-depth interviews, while secondary data are used for quantitative analysis. The result of the study shows that the â€œAyo Sekolahâ€ Program in Bojonegoro District that has been running since 2015 has significantly reduced dropout rates. The percentage of the drop-off rates for Bojonegoro Regency high school/vocational/MA in 2013-2017 decreased even though only 0.20 percent.